Problematika Pengajaran Bahasa Arab di Sekolah Dasar Islam Terpadu Pelita Khoirul Ummah Bandar Lampung - Orina, Dina; Lestari, Rahayu (CV. Creative Tugu Pena, 2024)
In the process of teaching Arabic in the school environment, difficulties are still found in delivering materials due to external or internal factors from the teacher. This research was conducted at SDIT Pelita Khoirul Ummah Bandar Lampung. This study aims to analyze the difficulties faced by teachers in teaching Arabic at the elementary school level. This type of research is field research which is descriptive qualitative. Data in this study were collected through interviews, observations and documentation of Arabic teachers in several elementary schools. The results of the study indicate that first, the lack of effective learning media to support the teaching and learning process, low motivation and interest of students in learning Arabic, educators/teachers do not have adequate educational backgrounds in teaching Arabic, the time provided for learning Arabic is considered insufficient to achieve optimal results, and social relations between teachers, students, and parents also affect the learning process. The results of this study show the difficulties faced by teachers in teaching and the efforts made to overcome the difficulties that occur. Further research will find even deeper difficulties.